Clinical effectiveness of customised sport shoe orthoses for overuse injuries in runners: a randomised controlled study. Issue 12 (12th August 2009) - Hirschmüller, A; Baur, H; Müller, S; Helwig, P; Dickhuth, H-H; Mayer, F
Abstract : Background and objectives: Treatment of chronic running-related overuse injuries by orthopaedic shoe orthoses is very common but not evidence-based to date. Hypothesis: Polyurethane foam orthoses adapted to a participant's barefoot plantar pressure distribution are an effective treatment option for chronic overuse injuries in runners. Design: Prospective, randomised, controlled clinical trial. Intervention: 51 patients with running injuries were treated with custom-made, semirigid running shoe orthoses for 8 weeks. 48 served as a randomised control group that continued regular training activity without any treatment. Main outcome: measures Evaluation was made by the validated pain questionnaire Subjective Pain Experience Scale, the pain disability index and a comfort index in the orthoses group (ICI). Results: There were statistically significant differences between the orthoses and control groups at 8 weeks for the pain disability index (mean difference 3.2; 95% CI 0.9 to 5.5) and the Subjective Pain Experience Scale (6.6; 2.6 to 10.6). The patients with orthoses reported a rising wearing comfort (pre-treatment ICI 69/100; post-treatment ICI 83/100) that was most pronounced in the first 4 weeks (ICI 80.4/100). Conclusion: Customised polyurethane running shoe orthoses are an effective conservative therapy strategy for chronic running injuries with high comfort and acceptance of injured runners.